2012
DOI: 10.1089/ten.tec.2011.0518
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Hypoxic Signaling in Encapsulated Stem Cells

Abstract: Oxygen is not only a nutrient but also an important signaling molecule whose concentration can influence the fate of stem cells. This study details the development of a marker of hypoxic signaling for use with encapsulated cells. Testing of the marker was performed with adipose-derived stem cells (ADSCs) in two-dimensional (2D) and 3D culture conditions in varied oxygen environments. The cells were genetically modified with our hypoxia marker, which produces a red fluorescent protein (DsRed-DR), under the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Insufficient nutrient and oxygen diffusion to the core of the capsules can activate hypoxia-inducible factor-1 alpha (HIF-1a) and lead to eventual necrotic cell death [54]. In this study, we found that encapsulated HLC remained viable for a week in culture suggesting sufficient diffusion of nutrients and oxygen to the core of the microcapsules.…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 68%
“…Insufficient nutrient and oxygen diffusion to the core of the capsules can activate hypoxia-inducible factor-1 alpha (HIF-1a) and lead to eventual necrotic cell death [54]. In this study, we found that encapsulated HLC remained viable for a week in culture suggesting sufficient diffusion of nutrients and oxygen to the core of the microcapsules.…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 68%
“…In the first experiment, MSCs were cultured as a two-dimensional monolayer on top of a thin gel (either 4mg/mL fibrin, 4F, or 4mg/mL PEGylated fibrin, 4P), eliminating gel-associated diffusion gradients (Sahai et al, 2012). Collagen was added as a third experimental group to control for fibrin content (4mg/mL collagen, 4C).…”
Section: Resultsmentioning
confidence: 99%
“…The threshold value was chosen such that no signal was detected in monolayer cells incubated in 20% O 2 , as levels of HIF-1a in these cultures were below detectable limits by western blotting in previous studies. 30 …”
Section: Fluorescent Cell Imaging and Image Analysismentioning
confidence: 99%